Industry 5.0 based on Hybrid and Nonlinear Systems in Robustness - Manikandan, K. P.; Saravanan, A.; Kadirvel, A.; Subramanian, D. Venkata; Jaganathan, Anitha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
For wireless communications offered by smart grid technology to be successfully integrated with Industry 5:0 applications, secure and dependable wireless communication technologies are necessary. Our paper presents some of the most current findings regarding hybridization techniques used in nonlinear system analysis. Utilizing the hybrid systems methodology as a methodical approximation technique is the fundamental concept of our hybridization strategy. An overview of current advancements in hybrid controller design for continuous-time control systems with differential state equations that are either linear or nonlinear is given in this work. For both linear and nonlinear systems, hybrid controllers offer an extension of classical feedback controllers. It is stressed that hybrid controllers have the advantage of being able to accomplish closed-loop performance goals that are unachievable with traditional linear or nonlinear controllers. In this paper, switching control architecture—a sort of hybrid controller—is presented, and an overview of newly created control strategies that make use of this control architecture is given. Through simulations with an example of a chemical process, the robust hybrid predictive control structure’s application and effectiveness are shown. As a result, the proposed theory offers a wealth of opportunities for further research into hybrid system stability and model predictive control, as well as for future practical applications.